Continence App: Construction and validation of a mobile application for postnatal urinary incontinence prevention. (September 2019) - Saboia, Dayana M.; Vasconcelos, Camila T.M.; Oriá, Mônica O.B.; de C Bezerra, Karine; Vasconcelos Neto, José Ananias; de M Lopes, Maria H.B.
Abstract: Objective: Describing the Continence App development as an educational technology to promote adherence to pelvic floor muscle training and prevent urinary incontinence in postpartum women. Study design: Study of technological production carried out in two stages: construction and validation. The first happened in four steps: modeling, navigation project, abstract design of the interface and implementation. In the validation phase 22 experts (11 health experts and 11 from the information technology/computing/communication areas) and 22 puerperal women were invited to evaluate the content and appearance of the education application. The content validity was analyzed through the Content Validity Index and the appearance validity through 75% minimum agreement in the items evaluated. The study was conducted during 2016 and 2017. For the content validation, the judges evaluated the following aspects: concepts and definitions used in the application, possibility of comprehension by the target audience and form of presentation. In order to validate the appearance, the installation, execution of the functions, objectives, usability, interface, practicality and interaction with the user were evaluated. Results: Most of health experts were physiotherapists ( n = 07) and professionals with a PhD ( n = 07). Regarding the CVI, 100% of the evaluated items obtained values of 0.86 or greater. Most of information technology/computing/communication experts were male (81.8%) and of the information technology area (63.6%). Except for "restart sessions", "ways of presenting suggestions", "user interaction" and "motivates questioning", all the other aspects received between 81.8% and 100% positive responses. All items evaluated by the target audience obtained a minimum of 94.3% positive responses from the participants. In this step, points for adjustment were identified in relation to the application content and interface, which were promptly corrected. Conclusions: The application has been validated for use in clinical practice as an educational technology to promote adherence to pelvic floor muscle training and prevention of urinary incontinence in postpartum women.